The Influence of the Fraud Pentagon on Financial Statement Fraud: Evidence from Financial and Banking Companies Listed on the Indonesia Stock Exchange from 2021 to 2024 - Krisna Amelia Tampubolon; Roni Budianto (Management Science Research Journal, 2026)
This study aims to identify the factors influencing fraudulent financial statements based on the fraud pentagon theory, proxied by financial target, ineffective monitoring, total accruals, director turnover, and political connections. Fraudulent financial statements are measured using the F-Score model. The sample consists of 396 observations from financial and banking sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Data were analyzed using panel data regression with STATA 17. The results indicate that financial target, ineffective monitoring, total accruals, and political connections do not have a significant effect on fraudulent financial statements. Meanwhile, director turnover has a negative and significant effect on fraudulent financial statements.